Intraoperative Use of Methylene Blue for Sentinel Lymph Node Detection in Breast Cancer Surgery: A Prospective Study - Abid Aziz, Muhammad; Bakhtiar, Nasir; Akhtar, Nasir Naseem; Ali Naper, Muhammad; Akbar, Fazli; Rizvi, Mohammad Basil (Journal of Neonatal Surgery, 2025)
Background: SLNB is suggested for breast cancer patients with histologically negative axillary nodes. It inhibits axillary lymph node dissection. Excellent intrinsic accuracy and low axillary nodal metastatic load (subject to patient selection) explain SLNB's low false negative rate, especially with blue dye. Location, injection site, mapping agent, volume, axillary nodal metastatic burden, and dissection competency impact SLN identification. Objective: The purpose of this research is to evaluate the efficacy of incisional and excisional biopsy methods for determining the rate of methylene blue injection into sentinel lymph nodes in patients with early-stage breast cancer. Methods:Participants in this study were women who had undergone a breast cancer biopsy and were in the early stages of the disease, meaning there was no lymph node metastases (N0). In this investigation, 110 people were considered. Methylene blue was injected into the peritumoral region before the sentinel lymph node biopsy. A positive lymph node biopsy result was indicated by blue nodes in the axilla, which were then sent for histopathology analysis. Results:In our study mean age of the included females was 47.13±10.76 years and had mean BMI 26.13±27.59 kg/m2. Majority of the cases 73 (66.4%) had tumor on right side of breast and 37 (33.6%) cases had tumor on left side.The sensitivity rate for patients who had excisional biopsy surgery was 84% and the specificity rate was 92%, whereas the accuracy rate for patients who had incisional biopsy surgery was 78% and the specificity rate was 81%. Conclusion: In this study, we found no difference in the accuracy of SLNB using methylene blue in patients with early-stage breast cancer with N0 and a history of either incisional or excisional biopsy.